脈動オーロラOFF時の輝度値の極端減少に関する統計解析 - 岸山, 泰輝; 細川, 敬祐; 野澤, 悟徳; 小川, 泰信; 大山, 伸一郎; 三好, 由純; 宮岡, 宏; 藤井, 良一; Taiki, Kishiyama; Keisuke, Hosokawa; Satonori, Nozawa; Yasunobu, Ogawa; et al. (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object